2021
DOI: 10.3390/ijms22094910
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Synovial Fluid from Rheumatoid Arthritis Patients Contain miRNAs with Capacity to Modulate Inflammation

Abstract: In rheumatoid arthritis (RA), extracellular vesicles (EVs) are associated with both the propagation and attenuation of joint inflammation and destruction. However, the specific EV content responsible for these processes is largely unknown. Investigations into identifying EV content are confounded by the challenges in obtaining high-quality EV preparations from synovial fluid. Implementing a size exclusion chromatography-based method of EV isolation, coupled with small RNA sequencing, we accurately characterise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Analyzing the composition of SF is helpful to clarify the pathogenesis and distinguishing biomarkers of IA. Recently, the function of exosomes in SF was established ( 15 , 16 ). Exosomes in SF can lead to inflammation, degeneration of cartilage, and destruction of joints ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the composition of SF is helpful to clarify the pathogenesis and distinguishing biomarkers of IA. Recently, the function of exosomes in SF was established ( 15 , 16 ). Exosomes in SF can lead to inflammation, degeneration of cartilage, and destruction of joints ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Urinary EVs’ isomiRs of miR-21, miR-204, and miR-375 are highly differentially expressed in prostate cancer individuals ( Koppers-Lalic et al, 2016 ), while urinary EV-increased expressions of miR-29a-3p and miR-200a-3p are altered in patients with nephropathy in Fabry disease ( Levstek et al, 2021 ). The altered EV miRNA levels are also reported in autoimmune diseases such as systemic lupus erythematosus, Sjogren’s syndrome, and type 1 diabetes ( Michael et al, 2010 ; Katsiougiannis et al, 2019 ; Tesovnik et al, 2020 ; Foers et al, 2021 ).…”
Section: Introductionmentioning
confidence: 87%
“…Because of their complex composition, EVs offer unique opportunities not only for early and precise detection of a disease, but also to obtain insights into the disease stage and its pathogenesis (Bongiovanni et al, 2021). For instance, a recent study has shown that EV miRNAs in synovial fluid are different in the joints of rheumatoid arthritis patients with high-and low-grade inflammation (Foers et al, 2021). Moreover, there is an upregulation of diseaseassociated miRNAs in brain-derived EVs in Alzheimer's patients, which has been exploited to establish the first early diagnostic blood test for a neurodegenerative disease (Cheng et al, 2020).…”
Section: Evs As Biomarkers With High Specificitymentioning
confidence: 99%